Use of Paxlovid in patients primary vaccinated against COVID-19 (Revista de Medicina Clinica, 2024)
Introduction: In March 2022, Spanish health authorities authorized the use of Paxlovid® (Nirmatrelvir, Ritonavir), primarily indicated for patients with immunosuppression, advanced age, or no prior vaccination. Objective: To compare the clinical and epidemiological characteristics between primovaccinated and non-primovaccinated patients with COVID-19 who received Paxlovid at the Ramón y Cajal University Hospital. Patients and methods: Patients over 18 years old who received Paxlovid between April 13 and August 31, 2022, were selected. Primovaccinated patients were defined as those who had received at least 3 doses of the COVID-19 vaccine. The distribution of clinical and epidemiological characteristics was compared using bivariate analysis between primovaccinated and non-primovaccinated patients with COVID-19. The Odds Ratio (OR) was used as a measure of association with a 95% confidence level. Results: A total of 107 patients received Paxlovid, including 82 primovaccinated and 25 non-primovaccinated individuals. Primovaccinated patients were older (74.9 vs. 55.9; p 0.016). There was a female predominance among non-primovaccinated patients (80%, p 0.06). Non-primovaccinated patients had more previous hospitalizations due to COVID-19 (24% vs. 3.66%; p 0.067). The most frequent pathological antecedents were neoplasms (> 43%). Pathological conditions associated with a high risk of severe COVID-19 were similar between primovaccinated and non-primovaccinated patients. Thirty-day outcomes following Paxlovid administration were worse among non-primovaccinated patients, with one death, one ICU admission, and two subsequent hospitalizations. Conclusion: Non-primovaccinated patients who received Paxlovid were younger, had more previous hospitalizations, and had worse outcomes.
Keywords: Immunosuppression; COVID-19 vaccine; Nirmatrelvir; Ritonavir